The "great live and move challenge": a program to promote physical activity among children aged 7-11 years. Design and implementation of a cluster-randomized controlled trial - Florence Cousson-Gélie; Marion Carayol; Bruno Fregeac; Lucile Mora; Florian Jeanleboeuf; Olivier Coste; Bruno Pereira; Mathieu Gourlan (BMC, 2019)
Abstract Background Recent population-based surveys have reported that large majorities of children in France, Europe and in the US are not complying with international physical activity (PA) guidelines. There is, therefore, a need to find programs that will improve children's PA habits from an early age. Theory-based interventions that include school, family, and community involvement have the potential to generate a considerable increase in the PA level of children. The theory of planned behavior (TPB) is one of the most widely tested models of the factors influencing health-related behaviors. The Great Live and Move Challenge (GLMC) is an extended TPB-based intervention designed to promote PA in French primary school children aged 7-11 years. The objective of this paper is to describe the protocol of a randomized controlled trial to evaluate the effectiveness of the GLMC on the PA level of children. Methods This is a two-year cluster-randomized controlled trial comparing an intervention group to a control group, randomized into clusters (community of communes) and stratified by department (Hérault, Gard, Aude) and residential environment (urban, rural). The goal is to recruit 4000 children. The GLMC involves children and their parents, and multiple local grassroots partners, such as school teachers, municipal officials and policy stakeholders. The intervention will be delivered over 3.5 months per year for a two-year period. Pre- and post-intervention, children and parents will be asked to fulfill a questionnaire concerning current PA level, TPB variables (i.e., intentions, attitudes, subjective norms, perceived behavioral control) and other psychosocial variables (e.g., perceptions of activity opportunities). A subsample of 400 children will be proposed to wear an accelerometer (i.e., the Actigraph GT3X+). The primary hypothesis is that the GLMC intervention will increase the proportion of children achieving the World Health Organization's recommended 60 min of moderate to vigorous PA per day by 15%. Discussion This study will evaluate the effectiveness of a multilevel, theory-based PA program and potentially provide valuable information for schools and public health officers looking for innovative PA programs. Trial registration ISRCTN:61116221, 19/06/2018.